Heidegger and the Poets: We Need to Talk About Trakl (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
Heidegger is well known for bringing philosophy and poetry together in fruitful ways. His essay, Language in the Poem: A Discussion on Georg Trakl's Poetic Work, poses questions about Heidegger's phenomenological method, when he states that 'every great poet creates his poetry out of one single poetic statement only', which he calls the 'site'. How is it that Heidegger takes this reductive view? This paper explores Heidegger's choice of 'site' and his discussion of it, that includes provocative views on nationalism and sexual difference. The problems of reading in translation are included in the discussion. Other readings of Trakl's work in an existential phenomenological frame are explored, along with the relevance this may have for psychotherapy.
Keywords: Heidegger; Trakl; poetry; psychotherapy; existential; translation